Who’s out there? A profile of informal traders in four South African city central business districts - Horn, Anele (Department of Urban and Regional Planning, University of the Free State, 2011)
The informal sector has gained prominence in developing countries during the past two decades, mainly as a result of the formal sector’s inability to absorb growing populations and an increasing number of individuals hoping to secure an income through selfemployment in the informal sector. The situation in South African cities is no exception as the unemployment rate has remained between 24% and 30% since 2000. The emphasis on informal trading in cities necessitates a more in-depth understanding of the informal sector and street traders at city level, for which relevant data are scarce or too general. By using data gathered among street traders in four major metropolitan areas of South Africa, this article seeks to provide a current profile of individuals that are involved in street trading in South African cities.

Die informele sektor het in ontwikkelende lande gedurende die laaste twee dekades in prominensie gegroei hoofsaaklik as gevolg van die formele sektor wat nie in staat is om die bevolkingsaanwas te absorbeer nie, en meer en meer individue wat hoop om ‘n inkomste te genereer deur middel van selfstandige werk in die informele sektor. Die situasie in Suid-Afrikaanse stede is geen uitsondering nie, ook in die lig van die werkloosheidskoers wat tussen 24% en 30% gewissel het sedert 2000. Die klem op informele handel in stede maak meer in-diepte kennis van die informele sektor en straatverkopers op stedelike vlak noodsaaklik. Relevante data hieroor is dikwels skaars en baie generies. Hierdie artikel maak gebruik van data wat ingesamel is onder straatverkopers in vier belangrike metropolitaanse gebiede in Suid-Afrika, om ‘n hedendaagse profiel saam te stel van individue wat betrokke is by straatverkope in Suid-Afrikaanse stede.

Barekisi ba seng molaong ba fumane monyetla wa ho rekisa dinaheng tse tswelang pele nakong ya mengwaha e mmedi e fetileng, lebakabaka e le ho sa kgone ha barekisi (borakgwebo) ba molaong ho kwenya ditjhaba tsena tse holang esitana le palo e eketsehang ya batho bana tshepang ho fumana tjhelete eo ba ka iphedisang ka yona ka ho itshebetsa tlasa barekisi ba seng molaong. Boemo metsemeholo ya ditoropo ya Afrika Borwa ha e na phapano ya letho ka ha tlhoko ya metsi e eme dipakeng tsa diphersente tse mashome a mabedi a metso e mene (24%) le mashome a mararo (30%) haesale ho tloha ka selemo sa 2000. Toboketso kgwebong ya barekisi ba seng molaong metsemeholo ya ditoropo e hloka kutlwisiso e tebileng ya barekisi ba seng molaong le barekisi ba mebileng boemong ba motsemoholo, moo dipalopalo di leng tlase kapa di bontsha kakaretso. Ka ho sebedisa dipalopalo tse bokeletsweng hara bahwebi ba mebileng metswemeholo e mene ya Afrika Borwa, ditaba tsena di batla ho fana ka nalane ya batho ba itseng ba keneng kgweboing ya mebileng metsemeholo ya Afrika Borwa.
Keywords: Developing countries; Self-employment; Informal sector